Different insulin treatment regimens in patient with diabetes mellitus type 1: Effects on quality of life - Stojanović Jelena; Milošević Dragoslav; Antović Ilija; Sekulić Goran; Beljić-Živković Teodora (Vojnosanitetski Pregled)
Background/Aim. Despite of contemporary diabetes mellitus (DM) treatment, one half of patients do not achieve an optimal metabolic control. Considering great psychological burden of diabetic patients, the purpose of this study was to assess the effect of different insulin treatment regimens, glycemic control and the presence of vascular complications on self-reported well-being and quality of life (QoL) of subjects with type 1 DM. Methods. The patients with type 1 DM (n = 122) recruited from the outpatient Diabetes Endocrinology Clinic of Zvezdara University Medical Center were divided into 4 groups according to the specific treatment regimen: 26 were on continuous subcutaneous insulin infusion (CSII), 30 on conventional insulin therapy, 33 on multiple daily injections (MDI) with human insulins, and 33 on MDI with insulin analogues. QoL was assessed by self-reported well-being with the following questionnaires: WHO-5 item Well Being Index (WHO- 5), 36 item Short Form (SF-36) survey, and Insulin Treatment Appraisal Scale (ITAS). Objective metabolic control was assessed by glycosylated hemoglobin (HbA1c), lipid levels and the presence of vascular complications. Statistical analyses used in this crosssectional study included: descriptive statistics, Student’s t-test, Chisqare test, contingency tables, ANOVA and correlation methods. Results. The patients on CSII had significantly better metabolic control than all other treatment groups, especially when compared to the one on conventional therapy (CSII HbA1c 7.07 ± 1.48% vs conventional therapy, HbA1c 10.04 ± 1.44; p = 0.000). No significant difference in glycemic control was observed between patients on MDI with human insulins and insulin analogues. Good glycemic control significantly influenced the reported QoL. The patients with retinopathy and nephropathy reported significantly lower physical well-being, and the patients with polyneuropathy and cardiovascular complications reported also lower psychological well being. Conclusions. Insulin treatment regiment selection affects not only objective metabolic control, but also QoL.